Sociological discourse in the Qur’an: human relation from perspective of the community development - Jassim, Layeth Suud (s.n, 2012)
It attempts to study the sociological discourse in the Qur'an in its different aspects. As we have known that guiding principles in the Qur'an is not confined in spiritual matters rather it is beyond the whole activities of mankind. The area of study is not do discuss it from philosophical or contemporary Islamic though in the hands of scholars of sociology